Toward a Community Geography Pedagogy: A Focus on Reciprocal Relationships and Reflection. Issue 1 (23rd November 2020) - Rees, Amanda; Hawthorne, Timothy; Scott, Dorris; Solís, Patricia; Spears, Eric
Abstract: Community geography (CG) pedagogy sits at the intersection of three systematic shifts in higher education: desires to expand engagement with society; the evolution of student-centered, evidence-based instruction; and, the desire to diversify voices and knowledge production in the academy. Since the 1960s geographers have regularly partnered with communities. However, within the last twenty years community geographers have centered community-engaged projects as the axis of each CG course, and combined pragmatism and service-learning to inform their instruction. Using five case studies we illustrate and provide recommendations for two key CG pedagogical characteristics: reciprocal partnerships and reflection.